2006
DOI: 10.1007/s11284-006-0151-4
|View full text |Cite
|
Sign up to set email alerts
|

Methods for estimating understory light conditions using crown projection maps and topographic data

Abstract: Four types of indices of canopy characteristics were compared to estimate understory light conditions using crown projection maps and topographic data. Crown area (CA) was formulated from the crowns in a focal sub-block (20 m·20 m). Canopy shade index (CSI) was formulated from the crowns in a focal sub-block and the surrounding sub-blocks with topographic effect. Site shade index (SSI) incorporated the shade of the slopes into CSI and represented the total physical closure of the site. Site light index (SLI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Hale 2003, Takashima et al 2006 and survivorship of equipment, we found a negative, but non-significant, relationship. A negative relationship suggests that increasing stand density, quantified in this case by the inverse of light penetration, may further mediate the degree of coastal protection that mangroves confer.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Hale 2003, Takashima et al 2006 and survivorship of equipment, we found a negative, but non-significant, relationship. A negative relationship suggests that increasing stand density, quantified in this case by the inverse of light penetration, may further mediate the degree of coastal protection that mangroves confer.…”
Section: Discussioncontrasting
confidence: 55%
“…Differences in light penetration among intact areas have been used as a proxy for stand density and stand structure in a number of forest types (e.g. Hale 2003, Takashima et al 2006 and references therein), which allows us to examine the effects of stand structure on the loss rate of experimental equipment in the intact areas.…”
Section: Methodsmentioning
confidence: 99%
“…The consistency of the derived light response between the two census intervals indicates that our light index contains information relevant to the species' performance. Interestingly, our light estimation procedure is similar to the index that best described gap light index obtained by hemispherical photographs in a temperate forest in Japan (Takashima, Kume & Yoshida 2006). The latter estimates also accounted for shading from topography, but we ignored this at BCI due to the relatively flat topography.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, digital hemispherical or fish-eye photography is becoming a common means for measuring LAI as well as studying canopy architecture and solar radiation in forests (Galhidy et al, 2006;Gendron et al, 2006;Jelaska et al, 2006;Jonckheere et al, 2006;Morsdorf et al, 2006;Wagner and Hagemeier, 2006;Domke et al, 2007). Hemispherical photographs have been widely used to measure canopy biophysical parameters (Rich, 1990;Chen and Black, 1991;Pellikka, 2001;Pellikka et al, 2000;Lovell et al, 2003), and to characterize daily and seasonal vegetation light environment (Capers and Chazdon, 2004;Gersonde et al, 2004;Tomita and Seiwa, 2004;Takashima et al, 2006). The recent advancement in digital cameras and image processing (WinSCANOPY, Regent Instruments, Ste-Foy, Quebec; Hemiview, Rich, 1990;Hemiphot, ter Steege, 1994;GLA, Frazer et al, 1997; CAN_EYE, http:// www.avignon.inra.fr/can_eye; DHP, Leblanc et al, 2005;CIMES, Walter, 2007) may have brought us a needed tool at an affordable rate to estimate biophysical parameters.…”
mentioning
confidence: 99%